Energy Evolution and Acoustic Emission Characteristics of Sandstone Specimens under Unloading Confining Pressure - Tao Qin; Yanwei Duan; Hongru Sun; Honglei Liu; Lei Wang (Shock and Vibration)
The acoustic emission characteristics of rock specimens under different initial unloading confining pressures were tested to obtain the damage and rupture characteristics of the sandstone unloading confining pressure path. The CT scan and three-dimensional reconstruction of the fractured rock specimens were carried out to study the differences of energy evolution and acoustic emission characteristics during the failure of sandstone under different initial unloading pressures. The results show that the unloading confining pressure has a significant influence on the deformation and failure of the rock. There is a significant yielding platform for the circumferential strain and the bulk strain at the peak of the unloading pressure. The larger the initial unloading pressure is, the greater the axial absorption strain energy, the dissipative energy, and the elastic strain energy are at the peak point. After the stress peak point, the elastic strain can be quickly converted into the dissipative energy for rock damage. The elastic energy released from the moment of rock failure under high confining pressure is more concentrated. The acoustic emission ringing and b value characteristic parameters of the rock have a good correlation with the internal energy evolution of the rock, which better reflects the progressive damage of the rock under low stress and the sudden failure of high-stress unloading.